DESKRIPSI HASIL BELAJAR SISWA DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Usman, Kartin; Djakaria, Ismail; Hasan, Salmiaty (Jurnal Karya Pendidikan Matematika, 2021)
This study describes students' mathematics learning outcomes in terms of their problem-solving abilities in rectangular material. The research was conducted at SMP Negeri 1 Suwawa in the odd semester of 2019/2020, with 22 students as research subjects. The research instrument used an essay test to measure students 'mathematics learning outcomes and interviews to obtain further information regarding students' mathematics learning outcomes. The indicators used to determine students' mathematics learning outcomes in terms of problem-solving abilities are 1) the ability to understand the problem; 2) the ability to plan problems; 3) problem-solving skills; 4) recheck ability. The results showed that the percentage of completeness of students' mathematics learning outcomes with high problem-solving abilities was 18.18%, the percentage of students' mathematics learning outcomes completeness with moderate problem-solving abilities was 68.18%, and the percentage of students' mathematics learning outcomes completeness with low problem-solving abilities was 68.18%. 13.64%.